Making sustainability work : best practices in managing and measuring corporate social, environmental and economic impacts - Epstein, Marc J., ....- (Sheffield, UK : Greenleaf Pub. ; San Francisco : Berrett-Koehler Publishers, 2008)
A thorough guidebook on strategies and best practices for corporate leaders, strategists, academics, and sustainability consultants.
Includes bibliographical references (p. [270]-281) and index.
Keywords: Corporations -- Environmental aspects; Duurzame ontwikkeling; Industries -- Environmental aspects; Social responsibility of business